Alkaloids from the roots of Stemona aphylla - Pitchaya Mungkornasawakul (2018)
Three known compounds, stemofoline (1), (2′S)-hydroxystemofoline (2), and (11Z)-1′,2′-didehydrostemofoline (3), along with two new alkaloids, stemaphylline (4) and stemaphylline-N-oxide (5), have been isolated from a root extract of Stemona aphylla. The structures of these alkaloids were determined on the basis of their spectroscopic data. The analysis of the crude dichloromethane extract by GC-MS in the EIMS mode showed the presence of alkaloids 1-4, the alkaloid 11, and stilbostemin R (12). The crude dichloromethane extract and 4 were tested for their comparative biological activities. The results of their acetylcholinesterase (AChE) inhibitory activities showed that the crude extract had higher activity than that of 4. The insecticidal properties of the crude extract and 4, using a topical application, showed that 4 had an activity similar to the positive control, methomyl, whereas the crude extract had much lower activity. Their antimicrobial activity against Escherichia coli ATCC 25922, Staphylococcus aureus ATCC 25923, Pseudomonas auruginosa ATCC 27853, and Candida albicans ATCC 90028 was weak (MIC 62.5-125 μg/mL, MBC 125-250 μg/mL, MFC 125 μg/mL) but much higher than that of the crude extract. © 2009 American Chemical Society and American Society of Pharmacognosy.